Chiropractic manipulative therapy of the thoracic spine in combination with stretch and strengthening exercises, in improving postural kyphosis in woman - Kim C. Branco; M. Moodley (AOSIS, 2016)
Purpose: This study serves to determine the effectiveness of either chiropractic spinal manipulative therapy to the thoracic spine or stretch and strengthening exercises (stretching the pectoralis major muscle and strengthening the rhomboid, middle and inferior trapezius muscles) versus the combined treatment of chiropractic spinal manipulative therapy to the thoracic spine in conjunction with stretch and strengthening exercises. Method: A randomised study design with thirty female participants between the ages of twenty and  thirty nine was selected. Group 1 (n = 10) received chiropractic spinal manipulative therapy to the thoracic spine. Group 2 (n = 10) received chiropractic spinal manipulative therapy to the thoracic spine as well as stretch and strengthening exercises i.e. stretching the pectoralis major muscles and strengthening the rhomboid, middle and inferior trapezius muscles. Group 3 (n = 10) received stretch and strengthening exercises. The stretch and strengthening exercises were performed in the consultation rooms to ensure that the participants were complying with the treatment and doing the exercises properly. The study consisted of seven consultations for Group 1 (they received treatment once a week for six weeks) and for Groups 2 and 3 there were nineteen consultations (they received three treatments a week for six weeks). Objective data was recorded at the beginning of the first, fourth and seventh consultations for Group 1, and the first, tenth and nineteenth consultations for Groups 2 and 3. On the seventh consultation (for Group 1) and nineteenth consultation for Groups 2 and 3, only data collection was done. Objective data were obtained by using the Flexicurve® Ruler measurements for the angle of kyphosis. Visual analysis was done by taking lateral (sagittal) view photographs at the beginning of the initial and final consultations. Results: Statistical analysis revealed significant statistical changes for the intragroup results for all three groups. No significant statistical difference was found between the groups for the inter-group analysis. Conclusion: The study showed that all three treatment protocols for Groups 1, 2, and 3 were effective. However, Group 1 had not shown a great improvement in their postural kyphosis, Group 3 had shown a relatively good improvement in their posture, while Group 2 had shown the best results with regards to improvement of the participants' posture. Therefore, in conclusion, Groups 2 and 3 treatment protocols can be used effectively to treat postural kyphosis but Group 2's treatment protocol, consisting of chiropractic spinal manipulative therapy to the thoracic spine in combination with stretch and strengthening exercises, will yield the best results.